Derivative securities pricing and modelling - Batten, Jonathan; Wagner, Niklas F., 1969- (Bingley, U.K. : Emerald, 2012)
This edited volume will highlight recent research in derivatives modelling and markets in a post-crisis world across a number of dimensions or themes. The book addresses the following main areas: derivatives models & pricing, model application & performance backtesting, new products & market features. Particular themes encompass: - continuous and discrete time modeling, - statistical arbitrage models, - arbitrage-free pricing, risk-neutral implied densities, - equilibrium pricing approaches (including e.g. co-integration), - applications of methods in computational statistics including simulation, - computationally intense techniques for pricing, estimation and backtesting, - complex derivative products, - credit and counterparty risk, - innovative market and product structures.
Derivatives securities pricing and modelling / Jonathan A. Batten, Niklas Wagner -- On the role of option applications in economic instability / Kavous Ardalan -- Derivatives, commodities, and social costs : exploring correlation in economic uncertainty / Aleksandr V. Gevorkyan, Arkady Gevorkyan -- Contingent capital securities : problems and solutions / Michalis Ioannides, Frank S. Skinner -- High dimensionality in finance : a graph-theory analysis / Delphine Lautier, Franck Raynaud -- Recovering stochastic processes from option prices / Jens Carsten Jackwerth, Mark Rubinstein -- The pricing kernel puzzle : reconciling index option data and economic theory / David P. Brown, Jens Carsten Jackwerth -- Risk-neutral densities and catastrophe events / Michael Herold, Matthias Muck -- Non-gaussian price dynamics and implications for option pricing / Miguel Angel Fuentes, Austin Gerig, Javier Vicente -- On the empirical behavior of stochastic volatility models : do skewness and kurtosis matter? / Marco M. García-Alonso, Manuel Moreno, Javier F. Navas -- Re-evaluating hedging performance for asymmetry : the case of crude oil / John Cotter, Jim Hanly -- On the binomial-tree approach to convertible bonds pricing and risk assessment / Krasimir Milanov, Ognyan Kounchev -- A new paradigm for inflation derivatives modeling / Lixin Wu -- An option-pricing framework for the valuation of fund management compensation / Axel Buchner, Abdulkadir Mohamed, Niklas Wagner -- An equity-based credit risk model / Gaia Barone -- Business cycles and the impact of macroeconomic surprises on interest rate swap spreads : Australian evidence / Victor Fang, A.S.M. Sohel Azad, Jonathan A. Batten, Chien-Ting Lin -- The evolution of the use of derivatives in Slovenian non-financial companies / Ales Berk Skok, Igor Loncarski, Matevz Skocir.
Includes index.
Print version record
Keywords: Business & Economics -- Finance; Financial reporting, financial statements; Financial crises & disasters; Derivative securities -- Prices -- Mathematical models; Derivative securities -- Prices